Urgensi Media Berbasis Komputer pada Perkembangan Bahasa Anak Usia Dini - Luluk Rochanah (SELING: Jurnal Program Studi PGRA, 2016)
Ability to know the letters in early childhood can not develop optimally if not followed by administration of stimulation (stimulating) motivation in children. If the learning relevant to the world of children, they will be happy child survive in these activities and are motivated to learn. Therefore it is very important for teachers to provide opportunities for children to see how useful it is to read and write before they dibelajarkan form and name the letters. It was supposed to be meaningful to the child means that the letters should be used by children in everyday real life, by giving a stimulus to motivate children to recognize letters to the utilization of computer media. Learning with computer media spawned a pleasant atmosphere for the child to control the pace of learning according to ability, color images and sound that appears to make children do not get bored, and stimulate more diligent, intelligent and creative and independent. Utilization of computer media is one of the alternative media used in making learning more fun so early childhood